Effectiveness of Alcohol Gel-Based Antiseptics Against Multidrug-Resistant Bacteria: An in vitro Experimental Study - Silva, Sacha Krolow e; de Deus, Larissa Britto; Bittencourt, Leonardo da Silva (ASIDE Health Sciences, 2025)
Background: Since the 19th century, asepsis has revolutionized public health, and hand hygiene remains a cornerstone of infection control, particularly in healthcare settings with high exposure to resistant microorganisms. This study aimed to evaluate the antimicrobial efficacy of four commercial alcohol-gel brands (A, B, C, and D) against standard ATCC strains of Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Enterococcus faecalis, which are prevalent in clinical environments.Methods: The disk-diffusion method was employed on Müeller-Hinton agar, using sterile disks impregnated with each gel sample. Following a 24-hour incubation at 35°C, the resulting halo zones were measured.Results: Significant variability was observed among the brands. Brand C exhibited the highest antimicrobial activity, particularly against P. aeruginosa (11.10 mm), with an overall mean inhibitory activity of 9.8 mm. Brand B demonstrated broad efficacy (mean 9.2 mm), while Brand A showed moderate activity with higher variability (mean 7.9 mm). Brand D demonstrated minimal to no inhibitory activity in the disk-diffusion assay compared to the other tested products (mean 4.3 mm). These differences were statistically significant across all tested bacteria.Conclusions: These findings indicate that alcohol concentration is not the sole determinant of antimicrobial performance. Formulation factors—such as humectants, polymers, and viscosity—substantially impact efficacy. The composition of an alcohol-based hand sanitizer directly governs its antimicrobial power. The study reinforces the importance of selecting validated products, adhering to hygiene protocols, and conducting microbiological surveillance to prevent healthcare-associated infections.